2012
DOI: 10.1016/j.bbr.2011.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the behavioral response to methylphenidate in three adolescent rat strains (WKY, SHR, SD)

Abstract: Methylphenidate (MPD) is the most widely used drug in the treatment of attention-deficit hyperactivity disorder (ADHD). ADHD has a high incidence in children and can persist in adolescence and adulthood. The relation between sex and the effects of acute and chronic MPD treatment was examined using adolescent male and female rats from three genetically different strains: spontaneously hyperactive rat (SHR), Wistar-Kyoto (WKY) and Sprague-Dawley (SD). Rats from each strain and sex were randomly divided into a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 76 publications
5
11
0
Order By: Relevance
“…The source of this discrepancy is unknown, but may have been due to the testing of multiple compounds (including nicotine), the strain tested (male Lister rats), or other procedural details including the route of administration and the temporal predictability of stimulus onset (see Bizarro et al., 2004 for discussion). Further, in our experiment, the increases in premature responses occurred in females, which is also consistent with previous findings with amphetamine in the choice reaction time task (Burton and Fletcher 2012), and in general with a greater sensitivity to psychostimulants in females (Becker et al 2001; Torres-Reveron and Dow-Edwards 2005; Roeding et al 2014; Bentley et al 2015; see Chelaru et al 2012 for strain-dependent differences).…”
Section: Discussionsupporting
confidence: 92%
“…The source of this discrepancy is unknown, but may have been due to the testing of multiple compounds (including nicotine), the strain tested (male Lister rats), or other procedural details including the route of administration and the temporal predictability of stimulus onset (see Bizarro et al., 2004 for discussion). Further, in our experiment, the increases in premature responses occurred in females, which is also consistent with previous findings with amphetamine in the choice reaction time task (Burton and Fletcher 2012), and in general with a greater sensitivity to psychostimulants in females (Becker et al 2001; Torres-Reveron and Dow-Edwards 2005; Roeding et al 2014; Bentley et al 2015; see Chelaru et al 2012 for strain-dependent differences).…”
Section: Discussionsupporting
confidence: 92%
“…The results from this study are in agreement with other studies on sex differences in response to MP and other psychostimulants that found that females showed greater levels of activity and exploration in open field than males when given oral MP (van Haaren and Meyer, 1991; Bethancourt et al, 2011). Females have generally been shown to be more sensitive to MP than their male counterparts, a finding that extends to other psychostimulants such as cocaine (Walker et al, 2001; Carrier and Kabbaj, 2012; Chelaru et al, 2012; Van Swearingen et al, 2013). …”
Section: Discussionmentioning
confidence: 96%
“…This discovery will likely increase ADHD diagnosis and subsequent treatment in females in the coming years, further supporting the need for research on possible sex differences in response to psychostimulant treatment. It has been well-documented that females are subject to different responses to drug treatments due to sex-specific pharmacological signaling differences, (i.e., growth development and hormonal distribution) (Brown et al, 2000; Zakharova et al, 2009; Tingen et al, 2010), and have been shown to be more sensitive to some of the effects of psychostimulants (Walker et al, 2001; Carrier and Kabbaj, 2012; Chelaru et al, 2012; Van Swearingen et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…The behavioral responses of rats to psychostimulants exhibit similar sex differences. Relative to males, female rats have enhanced responses to cocaine (COC) (Hu et al 2004; Kuhn et al 2001; van Haaren and Meyer 1991; Walker et al 2001; Walker et al 2009), MDMA (Walker et al 2007), methylphenidate (Chelaru et al 2012; Dafny and Yang 2006) and amphetamine (AMPH) (Beatty and Holzer 1978; Brass and Glick 1981; Robinson et al 1980; Stohr et al 1998). Females work harder for psychostimulants, learn to self-administer them faster, and are more sensitive to their rewarding effects than males (Anker et al 2011; Becker and Hu 2008; Davis et al 2008; Russo et al 2003b).…”
Section: Introductionmentioning
confidence: 99%